9514 1404 393
Answer:
- p(x) = (x+6)(x-3)(x-5)
- p(x) = (x-2)(x+2)(x^2 +36)
- p(x) = x^3 -7x^2 -x +7
- p(x) = x^4 -5x^2 -36
Explanation:
Each root r gives rise to a binomial factor (x-r). Each complex root also has a conjugate root, so roots ±ri give rise to a binomial factor (x^2 +r^2).
__
1. p(x) = (x -(-6))(x -3)(x -5)
p(x) = (x+6)(x-3)(x-5)
__
2. p(x) = (x -2)(x -(-2))(x^2 +6^2)
p(x) = (x -2)(x +2)(x^2 +36)
__
If you want standard form, you can start with factored form, then multiply it out.
3. p(x) = (x -1)(x +1)(x -7) = (x^2 -1)(x -7) = (x^2 -1)x +(x^2 -1)(-7)
p(x) = x^3 -7x^2 -x +7
__
4. p(x) = (x -3)(x +3)(x^2 +2^2) = (x^2 -9)(x^2 +4)
p(x) = x^4 -5x^2 -36